Peningkatan Keterampilan Membaca Puisi Pada Siswa Kelas X 1 Sma Muhammadiyah 3 Surakarta Melalui Metode Pembelajaran Scaffolding - Kisnaheni, Sri, Prof. Dr. Markhamah, M. Hum, Prof. Dr. Abdul Ngalim, M. Hum (2017)
The objectives of the research are to know and describe: 1) the implementation of contextual teaching and learning using scaffolding strategy in improving students' learning interest to Indonesian language learning in the competence standard of poetry reading; and 2) the implementation of contextual teaching and learning using scaffolding strategy in improving students' skills in interpreting poetry of X-1 grade students of the semester II in SMA Muhammadiyah 3 Surakarta academic year 2009/2010. The type of the research is classroom action research. The research was administered in class X-1 of the semester II in SMA Muhammadiyah 3 Surakarta academic year 2009/2010. The subjects of the research were X-1 grade students of the semester II in SMA Muhammadiyah 3 Surakarta academic year 2009/2010 consisted of 20 students. The object of the research was the implementation of contextual teaching and learning using scaffolding in Indonesian language learning in the competence standard of poetry reading. The data collecting methods were done using test, observation, and document techniques. The data analysis technique was done using Kemmis and Taggart model which aimed to identify the subjects' improvement having treated using special treatments in any specific period repeatedly until the program succeeded. The research concludes that: 1) The implementation of contextual teaching and learning using scaffolding strategy by paraphrasing and marking techniques may improve product effects in poetry reading skill of X-1 grade students of the semester II in SMA Muhammadiyah 3 Surakarta academic year 2009/2010. It is demonstrated with the improvement in students competence in poetry interpretation; 2) The implementation of contextual teaching and learning using scaffolding strategy by paraphrasing and marking techniques may improve process effects in learning of X-1 grade students of the semester II in SMA Muhammadiyah 3 Surakarta academic year 2009/2010, namely the students' learning interest. It is demonstrated with the improvement in students' learning interests score throughout the cycles. Keywords: poetry reading skills, scaffolding, paraphrasing, signing.